2020
DOI: 10.1007/s11581-020-03746-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene-like carbon attached porous silicon anode by magnesiothermic and nickel-catalyzed reduction reactions

Abstract: For improving performance of silicon anode in lithium ion batteries, a two-step preparation method was applied for synthesis of silicon carbon powder. The first step was to prepare Si/Ni composite powder by magnesiothermic reduction reaction in which Tetraethoxysilane (TEOS) was silicon source and NiCl 2 •6H 2 O was nickel source. The second step was to prepare silicon carbon in which triethylene glycol was carbon source and reduced by nickel catalyzed reactions on the surface of Si/Ni composite particles. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The carbon layer not only allows an electrical contact between Si particles and buffers the volume expansion of Si, but it also conjointly reduces the contact between the Si surface and the electrolyte; decreasing the decomposition of the electrolyte and improving the cycle life of the electrode (Table 1). Initially, there were few options for Si−C composites; typical methods included mixing Si powder with various carbonaceous materials, to obtain coated Si−C composites by ball milling [28,81]. An Si−C composite material with a coated core-shell structure has the following advantages: (1) improves the electrical conduction of electrons and ions; (2) provides mechanical support to adapt to the volume expansion of Si; and (3) isolates the Si and the electrolyte, to form a stable SEI film, thereby improving the first Coulombic efficiency (CE) [82].…”
Section: Coated Core-shell Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The carbon layer not only allows an electrical contact between Si particles and buffers the volume expansion of Si, but it also conjointly reduces the contact between the Si surface and the electrolyte; decreasing the decomposition of the electrolyte and improving the cycle life of the electrode (Table 1). Initially, there were few options for Si−C composites; typical methods included mixing Si powder with various carbonaceous materials, to obtain coated Si−C composites by ball milling [28,81]. An Si−C composite material with a coated core-shell structure has the following advantages: (1) improves the electrical conduction of electrons and ions; (2) provides mechanical support to adapt to the volume expansion of Si; and (3) isolates the Si and the electrolyte, to form a stable SEI film, thereby improving the first Coulombic efficiency (CE) [82].…”
Section: Coated Core-shell Structurementioning
confidence: 99%
“…Silicon is considered among the foremost anode materials with potential for nextgeneration LIBs [11]. However, during cycling, the volume of the silicon anode material expands (>300%) [25,26], the silicon particles crack and disintegrate, and then the inner resistance of the LIBs increases, diminishing its capacity [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…18 Zhang et al used tetraethoxysilane as a Si source and NiCl 2 •6H 2 O as a Ni source to prepare Si/Ni composites as anode materials through the magnesium thermal reduction reaction, which has good cycle performance. 19 In the 50th cycle, the specific discharge capacity of the Si/Ni composite powder was 415 mAh g −1 . Umirov et al first used the arc melting method and then the rapid solidification process to prepare Si−Ni alloys with different atomic ratios and good reversible capacity and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the synthesis temperature, heat control influences the morphology and microstructure of SiO x , which governs the electrochemical performance. [16][17][18][19][20][21][22][23][24][25] During magnesiothermic reduction, massive heat is released from the exothermic reaction (Mg [g], ΔH = À586.7 kJ mole À1 for SiO 2 ), 26 thereby increasing the temperature to a few hundred degrees higher than the set temperature. As a result, microstructural changes in SiO x , such as the formation of secondary phases (eg, Mg 2 Si and Mg 2 SiO 4 ) and abnormal growth of Si crystals, are induced.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we confirmed that the microstructural evolution of SiO x depends significantly on the temperature of the magnesiothermic reduction. In addition to the synthesis temperature, heat control influences the morphology and microstructure of SiO x , which governs the electrochemical performance 16‐25 …”
Section: Introductionmentioning
confidence: 99%